2016
DOI: 10.3341/jkos.2016.57.9.1354
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a New Non-invasive Tear Film Break-up Time Measurement Using a Keratograph

Abstract: Purpose:To evaluate the repeatability of non-invasive tear film break-up time and identify its relationships with dry eye parameters. Methods: A total of 100 participants (50 with dry eye, and 50 in the control group) were enrolled prospectively. Non-invasive keratograph first (NIKf-BUT) and average (NIKav-BUT) break-up times were evaluated 2 times using Keratograph 4 (Oculus, Wetzler, Germany), and then tear film break-up time with fluorescein (FBUT) was measured. The correlation analyses were performed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…NIKf-BUT was used in this study and the mean NIKf-BUT was 5.8 ± 2.0 seconds, which was longer than the FBUT, which was 5.2 ± 2.3 seconds. However, previous studies showed that the NIKBUT is shorter than the FBUT because software analysis of NIKBUT may detect very early tear film changes and heat from the LED (light emitting diode) may induce more tear break-ups [8,10,11]. In this study, the examiner subjectively measured the FBUT and did not use a stopwatch, which might have influenced these conflicting results.…”
Section: Discussionmentioning
confidence: 89%
“…NIKf-BUT was used in this study and the mean NIKf-BUT was 5.8 ± 2.0 seconds, which was longer than the FBUT, which was 5.2 ± 2.3 seconds. However, previous studies showed that the NIKBUT is shorter than the FBUT because software analysis of NIKBUT may detect very early tear film changes and heat from the LED (light emitting diode) may induce more tear break-ups [8,10,11]. In this study, the examiner subjectively measured the FBUT and did not use a stopwatch, which might have influenced these conflicting results.…”
Section: Discussionmentioning
confidence: 89%
“…TBUT <5 seconds was considered as severe dry eye, between 5–10 seconds as dry eye, and >10 seconds considered as normal. [ 8 , 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…Several causes contribute to the onset of dry eye symptoms after cataract surgery. The most important of them are decrease tear film breakup time due to surface irregularity at the site of the incision, prolonged use of antibiotic-steroid eye drops, poor tear film production and stability due to surgically induced ocular inflammation, decrease corneal sensation due to surgical incision which disrupts the cornea-lacrimal gland loop leading to reduced tear secretion, and exposure to light from the operating microscope [7,11,12] Various measurements are used to assess the incidence and severity pattern of dry eye syndrome among patients who have undergone phacoemulsification and extracapsular cataract extraction; such as: Schirmer tests, Invasive break up time test (IBUT) using fluorescein stain, and non-invasive break up time test (NIBUT) measured through video-keratography [13,14].…”
Section: Introductionmentioning
confidence: 99%